Improving classroom thermal comfort of educational buildings: Case of Kantipur City College - Moktan, Bilove; Uprety, Sanjaya (Journal of Engineering Issues and Solutions, 2023)
Well-designed and thermally comfortable learning spaces contribute to better academic performance, enhanced concentration, and improved productivity of students. Thermal comfort is often one of the most overlooked design parameters while constructing educational buildings in Nepal. The Nepalese government has yet to develop design guidelines or regulations which ensures optimum indoor thermal comfort. Due to this, classrooms either lack insulation, have poor ventilation, or have overall poor thermal performance. This study illustrates how the use of passive design measures such as thermal mass, insulation, and glazing can help in improving the thermal comfort of students in such classrooms. Kantipur City College, an engineering college in Kathmandu was selected as a case study to evaluate the thermal environment of the classrooms. The field study also determined the existing comfort levels of students based on their thermal sensations and preferences. Design Builder Software was used to carry out the thermal simulation analysis and evaluate the impacts of passive design strategies when applied to the base classroom model. Field survey showed that the indoor temperatures were in the range of 27-32 °C, and students felt quite uncomfortable during the lesson hours. Results from simulation analysis revealed that providing insulation to the walls and ceilings, applying thermal mass, or changing the window glazing lowered temperatures by 2-4 °C. The study concluded that careful consideration of appropriate passive design measures can help to significantly lower indoor temperature during the summer and maintain thermal comfort in the classrooms.